Physicochemical characteristics and metabolite content of roasted arabica coffee in relation to consumer preference - Tatsaporn Todhanakasem; Ngô Văn Tài; Kannika Kunyanee; Nateepat Pitinidhipat (LWT, 2025)
Roasting is probably the most important step in developing the complex flavors that make coffee enjoyable. During the roasting process, the beans undergo many complex reactions that change their biochemical and physical properties as well as form the substances responsible for the sensory qualities of the beverage. This study investigated the impact of roasting level (light, medium-light, or medium) on the evolution of coffee aroma, biochemical compounds, physical properties, and sensory characteristics in arabica coffee. The degree of roasting was directly correlated to the intensity of color development. The main volatile compounds that were commonly generated during roasting were 2-furancarboxaldehyde, furancarboxaldehyde-5-methyl, 2-furanmethanol, 2-furanmethanol-acetate, nonanal, camphor, 2-hexadecen-1-ol,3,7,11,15-tetramethyl-R-R∗,R∗-E, 2-furanmethanol, 2-furancarboxaldehyde-5-methyl, 2-furancarboxaldehyde, 2- furanmethanol-acetate, linalyl formate, citronellyl isobutyrate, and furfuryl pentanoate. Roasting coffee altered amino acid composition and the presence of bioactive compounds, including compounds potentially beneficial and unbeneficial with respect to human health. Regarding the sensory evaluation, there was no significant difference among roasting levels in overall liking, liking of overall aroma, coffee flavor, sourness, bitterness, body, or coffee aftertaste. However, the medium-light condition generated sensory attributes of roasted, bitter, jasmine, coffee aftertaste, smoky, nutty, and coffee flavor that tended to be more favorable to the consumer. This study provides valuable enlightenment on the impact of roasting degree in relation to coffee quality. • Effects of roasting levels of arabica coffee on aroma, physicochemical properties, sensory and consumer preferences. • Diversity in aroma and biochemical compounds produced at the different coffee roasting level. • The guidance on the most effective roasting process to develop premium coffee suited to health and taste.
Keywords: Coffee research and impacts; GABA and Rice Research; Food Chemistry and Fat Analysis